Use of Electroconvulsive Therapy in Dementia-Related Agitation: A Case Series. Issue 4 (December 2017) - Burton, M. Caroline; Koeller, Sandra L.; Brekke, Frank M.; Afonya, Adonye T.; Sutor, Bruce; Lapid, Maria I.
Abstract : Objectives: This naturalistic prospective observation study examines the efficacy of electroconvulsive therapy (ECT) in treating dementia-related agitation. Methods: Patients with dementia-related agitation who received ECT were compared with patients with the same condition who did not receive ECT using Cohen-Mansfield Agitation Inventory (CMAI), Neuropsychiatric Inventory (NPI)—nursing home version, and Clinical Global Impression Scale (CGI). Outcomes were compared between ECT-treated and non–ECT-treated patients. Results: A total of 9 patients were included in the study. Six received ECT, and 3 did not. Patients in the ECT and non–ECT-treated groups had comparable baseline scores (CMAI, P = 0.880; NPI, P = 0.814; and CGI, P = 0.445). The CMAI, NPI, and CGI scores were lower on final assessment in both groups with no statistically significant difference (CMAI, P = 0.771; NPI, P = 0.243; and CGI, P = 0.519). Conclusions: Electroconvulsive therapy should be considered as a treatment option in the management of severe treatment refractory dementia-related agitation.